Reducing Suppressors of Cytokine Signaling-3 (SOCS3) Expression Promotes M2 Macrophage Polarization and Functional Recovery After Intracerebral Hemorrhage - Ji, Xin-Chao; Shi, Ya-Jun; Zhang, Yan; Chang, Ming-Ze; Zhao, Gang (Frontiers in Neurology, 2020)
Intracerebral hemorrhage (ICH) is a fatal subtype of stroke, and effective interventions to improve the functional outcomes are still lacking. Suppressor of cytokine signaling 3 (SOCS3) plays critical roles in the inflammatory response by negatively regulating cytokine-Jak–Stat signaling. However, the role of SOCS3 in the regulation of macrophage polarization is highly controversial and the fine regulation exerted by SOCS3 needs further understanding. In this study, rat ICH models were established by infusion of collagenase into the caudate nucleus. To decrease SOCS3 expression into microglia/macrophages in the hemorrhagic lesion area, we injected lentiviral short hairpin RNA (shSOCS3) (Lenti-shSOCS3) into the hematoma cavity at 24 h following ICH. We found that the number of iNOS-positive cells (M1 phenotype) was significantly reduced, whereas arginase-1-positive cells (M2 phenotype) were markedly elevated in animals that received Lenti-shSOCS3 injections compared with those in the Lenti-EGFP and saline groups. The increase in arginase-1-positive cells was associated with a significantly lower pro-inflammatory microenvironment, which included the downregulation of pro-inflammatory cytokines [interleukin (IL)-1β, IL-6, and TNF-α] and concurrent upregulation of anti-inflammatory (IL-10) mediators. In addition, this marked shift toward the M2 phenotype was associated with suppressed NF-κB activation. Furthermore, these changes notably enhanced the neuroprotective effects and functional recovery in Lenti-shSOCS3-injected animals. Our findings indicated that reduction in SOCS3 expression caused a marked bias toward the M2 phenotype and ameliorated the inflammatory microenvironment, which enhanced neuroprotective effects and resulted in notable improvement in functional recovery after ICH.